1996
DOI: 10.1111/j.1600-051x.1996.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Root cleaning or root smoothing An in vivo study

Abstract: The goal of the present study was to determine whether the clinical treatment results in terms of pocket probing depth reduction and attachment gain would be different following conventional periodontal flap surgery if, on the one hand, root surfaces were smoothed after plaque and calculus removal or, on the other hand, root surfaces were first thoroughly cleaned but then intentionally roughened. 13 adult patients with moderate periodontitis participated; the same patients acted as a unit of control. Evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…27 However, smooth root surfaces are not a perquisite for a successful SRP. 28,29 Smooth root surfaces at the gingival margin are advantageous because the odds of dental plaque accumulation on smooth surfaces are less than that on rough surfaces and the efficacy of plaque removal from the smooth surfaces is higher than that from rough surfaces. Some studies 30,31 have shown that surface roughness due to subgingival SRP significantly increases subgingival microbial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, smooth root surfaces are not a perquisite for a successful SRP. 28,29 Smooth root surfaces at the gingival margin are advantageous because the odds of dental plaque accumulation on smooth surfaces are less than that on rough surfaces and the efficacy of plaque removal from the smooth surfaces is higher than that from rough surfaces. Some studies 30,31 have shown that surface roughness due to subgingival SRP significantly increases subgingival microbial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…But a smooth surface may be advantageous near the gingival margin, since a smooth surface is less likely to accumulate plaque than a rough surface. [33]…”
Section: Discussionmentioning
confidence: 99%
“…Although the roughness of the root surface does not seem to interfere with periodontal healing the diagnosis of remaining subgingival calculus on a rough root surface might be hampered [23]. Consequently an instrumentation method which creates rough dentine surfaces carries the risk of overinstrumentation on the one hand side and remaining undiagnosed calculus on the other hand.…”
Section: Discussionmentioning
confidence: 99%